Diet and breeding habitat preferences of White-tailed Eagles in a northern inland environment - Ekblad Camilla; Tikkanen Hannu; Sulkava Seppo; Laaksonen Toni (Springer, 2022)
Many apex predator populations are recolonizing old areas and dispersing to new ones, with potential consequences for their prey species and for livestock. An increasing population of the White-tailed Eagle (Haliaeetus albicilla) has settled north of the Arctic Circle in northern Finland, mainly at two big water reservoirs but also in areas with mainly terrestrial habitat. We examined nesting habitat preferences and prey use of White-tailed Eagles in this environment, where reindeer husbandry is a traditional livelihood and concerns are rising that the growing White-tailed Eagle population poses a threat to reindeer calves. Lakes, peat bogs, and marshlands were preferred habitats in the nesting territories. Fish constituted 64.3% of the identified prey items, with birds accounting for 28.5% and mammals 7.2%. The nesting territory habitat within a 10 km radius and the latitude influenced the prey composition at both the group and species level. The occurrence of reindeer calves as prey increased with latitude but was not associated with any habitat. Knowledge of the diet and territory preferences can be used to predict future dispersal and local prey use of this species. Nesting White-tailed Eagles do not seem to pose a threat to traditional reindeer herding, but further research is needed regarding non-breeding sub-adults and whether the White-tailed Eagles actually kill reindeer calves or simply exploit their carcasses.